The SHI irradiation induced transition to negative dielectric constant phase in K2Bi4Ti4WO18 - Sharma, Vipul K.; Kumawat , Ashish K.; Rathore , Satyapal S.; Sulania , Indra; Meena , R. C.; Kedia, S. K.; Nathawat, Dr. Rashi (Frontiers in Physics, 2023)
In the present communication, a new Aurivillius family compound K2Bi4Ti4WO18 was synthesized, and the impact of Swift Heavy Ion (SHI), Ni+11 irradiation on its surface, and dielectric properties has been studied in detail. The phase formation in this complex oxide, and crystallization to B2cb symmetry was confirmed by the X-ray diffraction. However, post irradiation the XRD, SEM and AFM studies shows surface amorphization, in agreement with the theoretical calculations. Furthermore, the effect of irradiation was also observed in the bulk dielectric properties as the system transform to a phase with a negative dielectric constant above 350 K in the radio frequencies. This transition is in correlation with a significant change in other dielectric parameters such as enhancement in AC conductivity, a helical Nyquist plot, and multiple dielectric relaxations. These conspicuous changes in the dielectric response post irradiation is attributed to the SHI induced defect formation, modification of energy barriers, and their consequences on the electronic structure. Thus, the current study suggests that the dielectric properties of Aurivillius K2Bi4Ti4WO18 could be tailored by ion irradiation and opens a new possibility of tuning functional properties.